STUDI KOMPARATIF TERJEMAHAN BUKU MULAKHKHAS{ QAWA'ID AL-LUGHAH AL-‘ARABIYYAH KARYA FUAD NI'MAH OLEH ABU AHMAD DAN QUILLBOT.AI - Muchammad Rizqi Aminudin; Syihabbudin Syihabbudin; Mia Nurmala (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to compare the translation quality of Arabic texts from Mulakhkhas Qawa'id Al-Lughah Al-‘Arabiyyah by Fuad Ni'mah, translated by Abu Ahmad Al-Mutarjim and by the machine translation tool QuillBot.Ai. A qualitative descriptive approach is employed, using Peter Newmark's translation theory as the analytical framework, particularly focusing on the aspects of accuracy, acceptability, and clarity. The data consists of vocabulary and sentence structures analyzed to evaluate how well each translator conveys the original meaning of the text into Indonesian.The findings reveal that the human translator performs better in preserving the context, structure, and intended meaning of the original text. In contrast, QuillBot.Ai tends to produce meaning distortion and lacks conformity to proper linguistic norms in Indonesian. This suggests that although machine translation can assist in translation tasks, human intervention remains crucial, especially in translating scientific and religious texts.This study contributes to the understanding of the limitations of machine translation and recommends further research into human-machine collaboration in translation practices.